Clinical profile of patients with acute coronary syndrome and its association with biomarker troponin I - S. Joshi, Hemant; Sajal, Samil; Yagnik, Nirmit V.; Bolya, Y. K. (International Journal of Advances in Medicine, 2018)
Background: In patients with acute coronary syndromes, it is desirable to identify a sensitive serum marker that is closely related to the degree of myocardial damage, provides prognostic information, and can be measured rapidly. Author studied the clinical profile of patients with Acute MI and its relation with troponin I level. Methods: In this prospective study, 65 patients admitted with Acute MI were studied. Study patients were divided in Troponin I positive and Troponin I negative group. Patients were followed up to discharge or death in the hospital. Results: Most common symptom present in the patients with Acute Coronary Syndrome was chest pain (94%) and most common risk factor was dyslipidaemia (72.3%). Most common complication was recurrent angina (72.3%). Out of total patients with significant CAD, almost 70 % belong to Troponin I positive group and it is statistically highly significant (p<0.05). Total 30 patients (46.2%) have more than 10 episodes of angina in our study. There is statistically significant association between number of angina episode and Troponin I positivity (p<0.05). Out of total deaths, 73.3% have occurred among Troponin I positive study patients and it is statistically significant (p<0.05). Conclusions: In patients with acute coronary syndromes, cardiac troponin I levels provide useful prognostic information and permit the early identification of patients with an increased risk of death.